2013
DOI: 10.1038/nchembio.1213
|View full text |Cite
|
Sign up to set email alerts
|

A single-molecule dissection of ligand binding to a protein with intrinsic dynamics

Abstract: Protein dynamics have been suggested to have a crucial role in biomolecular recognition, but the precise molecular mechanisms remain unclear. Herein, we performed single-molecule fluorescence resonance energy transfer measurements for wild-type maltose-binding protein (MBP) and its variants to demonstrate the interplay of conformational dynamics and molecular recognition. Kinetic analysis provided direct evidence that MBP recognizes a ligand through an 'induced-fit' mechanism, not through the generally propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
157
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 113 publications
(161 citation statements)
references
References 44 publications
4
157
0
Order By: Relevance
“…The transitions between the two distinct conformational states were clearly detected. As previously reported 12 , the low-and high-FRET states were interpreted as open and partially closed forms, respectively. The intrinsic dynamics of the other MBP mutants could also be observed with a 100-ms time resolution in smFRET measurements ( Supplementary Fig.…”
Section: Construction Of Mbp Mutants With Varying Binding Affinitiesmentioning
confidence: 98%
See 4 more Smart Citations
“…The transitions between the two distinct conformational states were clearly detected. As previously reported 12 , the low-and high-FRET states were interpreted as open and partially closed forms, respectively. The intrinsic dynamics of the other MBP mutants could also be observed with a 100-ms time resolution in smFRET measurements ( Supplementary Fig.…”
Section: Construction Of Mbp Mutants With Varying Binding Affinitiesmentioning
confidence: 98%
“…The receptor-ligand interaction process comprises two fundamental steps, namely, the binding and dissociation of a ligand. Our recent single-molecule studies revealed that conformational dynamics plays a negligible role in the ligandbinding step of an MBP 12 . A series of MBP mutants constructed through hinge mutations were shown to have a wide range of intrinsic opening rates and dissociation constants for maltose, enabling us to investigate how protein dynamics determine the ligand dissociation, and thus the binding affinity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations